Influence of palm oil biomass clinker and empty fruit bunch fibers on concrete properties - Putra Jaya, Ramadhansyah; Mohd Haziman, Wan Ibrahim; Mangi, Sajjad Ali; Sharifah Salwa, Mohd Zuki; Supriyatno, Dadang (IIUM Press, 2020)
This study aims to evaluate the influence of palm oil Empty F r ui t Bunch (EFB) fiberson flexural strength performance of concrete in the presence of Palm Oil Biomass Clinker (POBC). This study considered various proportions of palm oil EFB fibersas 0%, 0.2%, 0.4%, and 0.6% in concrete with fixed amount of POBC as 10% . I t was investigated that there is substantial influence of palm oil EFB fibers on properties of concrete containing 10% POBC as sand replacement. The experimental findings of this study indicated that the workability of fresh mix concrete decreases as palm oil EFB fibercontent increased. Besides that, hardened properties of concrete were found to be improved asthe amount of palm oil EFB fibers increased in the concrete. It was not iced that flexural strength was improved with addition of 0.2% palm oil EFB fibers that act as reinforcement and deliver growth in flexural strength for concrete containing 10% of POBC. Hence, it was concluded that palm oil EFB fibercould be utilized as fiberreinforcement in concrete to improve flexural strength performance of the concrete.